Analisis Pengaruh Perceived Risk dan Trust terhadap Pengujian Behavioral Intention Mahasiswa Pengguna GoPay - Antonius Prasetyo; Aurelia Melinda Nisita Wardhani (EXERO : Journal of Research in Business and Economics, 2022)
This study aims to examine behavioral interest in GoPay user students in the Province of the Special Region of Yogyakarta with the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model, perceived risk, and trust. This research is expected to contribute to solving the problem of GoPay user interest, developing the GoPay system, accelerating the cashless society in Indonesia, and slowing the spread of the Corona virus. This study uses a survey method for distributing questionnaires online. Respondents in this study amounted to 321 students. The sampling technique was carried out using the snowball sampling technique. The data analysis tool in this study uses SmartPLS 3.3.3. The result of this study is that the behavioral intention of students to use GoPay has a positive effect on social influence, hedonic motivation, habit, and trust. On the other hand, performance expectancy, effort expectancy, facilitating conditions, and price value do not have a positive effect on the behavioral intention of students using GoPay in the Special Region of Yogyakarta. Perceived risk does not have a negative effect on the behavioral intention of students using GoPay in the Special Region of Yogyakarta.